2022
DOI: 10.1007/s00423-022-02540-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective decontamination of the digestive tract in colorectal surgery reduces anastomotic leakage and costs: a propensity score analysis

Abstract: Purpose Anastomotic leakage (AL) and surgical site infection (SSI) account for most postoperative complications in colorectal surgery. The aim of this retrospective trial was to investigate whether perioperative selective decontamination of the digestive tract (SDD) reduces these complications and to provide a cost-effectiveness model for elective colorectal surgery. Methods All patients operated between November 2016 and March 2020 were included in our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Anastomotic leakage rates ranged from 4.3% [ 26 ] to 29.8% [ 21 ]. Three studies reported the severity of AL either according to the International Study Group of Rectal Cancer classification Grade A–C [ 28 , 30 ] or to the severity of peritoneal contamination [ 4 ], and 7 out of 17 studies reported the rate of diverting ostomy during index surgery [ 4 , 22 , 24 , 26 , 28 , 29 , 33 ], of which the highest reported rate was by Ashraf et al. [ 4 ] at 37.2% and the lowest rate by la Regina et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic leakage rates ranged from 4.3% [ 26 ] to 29.8% [ 21 ]. Three studies reported the severity of AL either according to the International Study Group of Rectal Cancer classification Grade A–C [ 28 , 30 ] or to the severity of peritoneal contamination [ 4 ], and 7 out of 17 studies reported the rate of diverting ostomy during index surgery [ 4 , 22 , 24 , 26 , 28 , 29 , 33 ], of which the highest reported rate was by Ashraf et al. [ 4 ] at 37.2% and the lowest rate by la Regina et al.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of the majority of the included studies was the limited time span. The cost calculation was based on AL identified either during index hospitalization [ 4 , 21 , 29 , 30 , 33 , 35 , 36 ] or within 30 days postoperative [ 22 , 24 , 28 , 32 , 34 ] in the majority of the studies. However, restorative surgical procedures after AL are usually performed more than 30 days after index surgery, so these costs were not included in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies [35][36][37] used PTV (=polymyxin B (or E), tobramycin and vancomycin but no gentamicin) and reported, respectively, a reduction in AL from 14.9% to 6.5%, 20% to 5% and 10.6% to 2.9%. Also, these three studies investigated elective patients only.…”
Section: Results Of Interventions For Preventing Al In the Previous L...mentioning
confidence: 99%
“…The next study by the group of Schardey [36] was cancelled after an interim analysis because of a death in the control group, not in the group using the investigation drug. This setting and concept were also investigated by a group of German researchers at the University of Dresden [37] for elective patients only, and it resulted in a reduction in AL in the decontamination group.…”
Section: Discussion Of Former Findings In the Literaturementioning
confidence: 99%
See 1 more Smart Citation